PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PENYAKIT MENULAR SEKSUAL DI SMAN 3 KOTA SUKABUMI - Astiti Gustiyana; Ariesta Fitrianindyah Yudha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract : Sexually Transmitted Disease is a clinical syndrome and infection caused by pathogens and transmitted from one person to another transmission can occur even if you only have sexual intercourse once without using a condom with a person with a sexually transmitted disease (Purba Rahayu 2021). This study aims to determine the influence of health education on the level of knowledge of adolescent girls about sexually transmitted diseases. This study uses a quantitative research method with an experimental design This research uses a posttest with control design, which is a research activity that provides an initial test (pretest) before being given treatment, after being given a final test (posttest) with statistical analysis using the Wilcoxon test. This study was conducted at Sman 3 in Sukabumi city in march – May 2026, The population in this study is all adolescent girls in class XI with a sample of 60 people. The results showed that the level of knowledge of adolescent girls about sexually transmitted diseases in the intervention group before being given health education was less than the average level of knowledge (66.6%) and experienced a significant increase after being given health education, namely with an average of sufficient knowledge (80%). Meanwhile, in the control group when the pretest was carried out, the level of knowledge was less on average (80%) and when the posttest was carried out, the results of the knowledge level were less on average (66.6%). This shows that adolescents with good knowledge of the intervention group and the control group have a difference of 73.4%.